68.8k views
4 votes
Which expression is equivalent to: (x +9)(x+3)

a. x2 + 6x + 6
b. x2+27x+12
c. x2+ 12x+27
d. x2+ 12x + 12

2 Answers

3 votes

Answer:

c

Explanation:

x*x=x^2

x*9=9x

x*3=3x

9x+3x=12x

9x3=27

x^2+12x+27

User AkaBase
by
4.6k points
1 vote

Answer:

C

Explanation:

To solve use the FOIL method, First, Outside, Inside, Last. This means to multiply the first terms, the ones on the outsides, the ones on the insides, and finally the last ones.

First, multiply x*x=
x^(2)

Then, multiply x*3= 3x

Next, multiply 9*x= 9x

Finally, multiply 9*3= 27

To simplify put all of the products together,
x^(2)+3x+9x+27, then add like terms
x^(2)+12x+27, so the answer is C.

User Keltar
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.